2018
DOI: 10.12973/eu-jer.7.4.849
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Views of Pre-Service Teachers on the Use of Augmented Reality Applications in Education

Abstract: It was aimed in this study to determine the teacher candidates' views on the augmented reality applications in education. It is a descriptive study to identify the present situation. Survey model, one of the quantitative research methods, was used in the research. The sample group of the study is comprised of 220 teacher candidates who are studying in the 2nd Grade of 8 departments in Mersin University Faculty of Education. Consisting of 4 sections, 22 items and an open-ended question, a questionnaire was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
11
0
2
Order By: Relevance
“…Moreover, AR is friendly and able to be supplemented with instruction (Syawaludin, Rintayati, & Subiyantoro, 2020). According to Uygur et al (2018), AR applications are very entertaining, motivating, and facilitate learning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, AR is friendly and able to be supplemented with instruction (Syawaludin, Rintayati, & Subiyantoro, 2020). According to Uygur et al (2018), AR applications are very entertaining, motivating, and facilitate learning.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm Chookaew et al (2017), which stated that AR-based learning motivated to build teaching materials, helping them prepare as prospective teachers. Also, Uygur et al (2018) stated that the use of AR technology motivates and facilitates learning for prospective teachers. These results are in line with previous studies, which found that the integration of AR technology with local wisdom increases PSMT learning (Sudirman, Yaniawati, Indrawan, & Melawaty, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AR links information to real life situations when bringing it to the classroom, thus makes learning easier. According to the study Uygur et al (2018) conducted with trainee teachers, AR's visualization aspect helped the trainees to understand difficult subjects with ease and to retain information permanently.…”
Section: Introductionmentioning
confidence: 99%